Conjugated Nanohoops Incorporating Donor, Acceptor, Hetero‐ or Polycyclic Aromatics. Issue 29 (22nd March 2021) - Hermann, Mathias; Wassy, Daniel; Esser, Birgit
Abstract: In the last 13 years several synthetic strategies were developed that provide access to [n]cycloparaphenylenes ([n]CPPs) and related conjugated nanohoops. A number of potential applications emerged, including optoelectronic devices, and their use as templates for carbon nanomaterials and in supramolecular chemistry. To tune the structural or optoelectronic properties of carbon nanohoops beyond the size‐dependent effect known for [n]CPPs, a variety of aromatic rings other than benzene were introduced. In this Review, we provide an overview of the syntheses, properties, and applications of conjugated nanohoops beyond [n]CPPs with intrinsic donor/acceptor structure or such that contain acceptor, donor, heteroaromatic or polycyclic aromatic units within the hoop as well as conjugated nanobelts. Abstract : Designer hoops: By incorporating aromatic units with specific electronic (i.e. donor/acceptor) or structural (i.e. chirality) properties, it is possible to modify cycloparaphenylenes and conjugated hoops according to design. This Review provides an overview of such structurally designed hoops, their structural, optoelectronic, and host properties, and potential (future) applications.